Estresse eletromecânico em transformadores causado por curtos-circuitos passantes e correntes de energização - Azevedo, Ana Claudia de (2007)
Power transformers are quite costly and essential to provide reliable electrical power system operation. Besides their maintenance or substitution costs, transformer failures must be taken into account, since its will have a large impact on the utility financial health due to the temporary loss of power delivery capability. Concerning transformer failure statistics, investigations carried out in many utilities in the world reveal that the effect of electromechanical stress caused by short-circuit currents is a relevant cause of failure in such equipment and they cause onerous financial damage. Failures caused by mechanical stress due to external short-circuit and due to inrush currents are an important aspect to be considered. The excessive strength caused in transformer conductors/windings due to electromagnetic forces can reduce the transformer lifetime or even cause irreversible damages of them. Therefore, the investigation of the harmful effects caused by transient phenomena becomes imperative. With this in mind, this work aims at investigating the electromagnetic forces and mechanical stresses due to external short-circuit and inrush currents inside the transformer. The studies are carried out using a time domain transformer model based on magnetomotive forces and magnetic reluctances, which allows simulating the transformer transient and steady state behavior regarding the electric, magnetic and mechanical aspects. The methodology is applied in two transformer models operating under rated and short-circuit conditions. Due to the lack of mechanical stress experimental values, a comparative performance analysis is obtained by comparing the simulated results and the well accepted results from finite element program. The results obtained from simulations are evaluated through of the impacts provoked in the variables used to analyze the mechanical stresses which occur in the transformers due to short-circuit and inrush currents. From the mechanical stress calculated it is presented a methodology that establishes a correlation between the phenomena here investigated and the impact in the transformer lifetime. This can assist, previously, in the reduction of the number of unexpected failures and, consequently, in financial damages.